Malaysia’s Domestic Value Added Export: The Role of Governance and Strategic Policy Reforms - Sahu, Pritish Kumar (International Journal of Economics and Financial Issues, 2016)
This paper evaluates Malaysia’s value added export (VAE) in the light of its strategic policy reforms and governance. First, the study proposes a conceptual framework to show the role of governance and policy reforms in shaping a country in the path of VAE. Later, it undertakes an empirical analysis to evaluate the success of Malaysia’s VAE with the help of WTO-OECD Trade in Value Added (TiVA) database from 1996 through2014. The empirical findings reveal a significant relationship between VAE and the governance indicators and the policy parameter proxies, indicating that the government plays a significant role in Malaysia’s increased VAE. Keywords: Value Added Export; Trade; government Policies; Governance indicators; Tariff; TiVA JEL Classifications: F13; F15; F23; F43